Comparison of Outcomes Following Severe TBI Between Pediatric and Adult Patients With Similar GCS and Pupil Parameters - Obaid, Ramsha Nasir; Khan, Atiq Ahmad; Shah, Irfan Ali; Ahmed, Shiraz; Shahnawaz, Shahida; Bin Sultan, Syed Muhammad Moaaz (Biological and Clinical Sciences Research Journal, 2025)
Severe traumatic brain injury (TBI) remains a leading cause of mortality and long-term disability across all age groups. Pediatric patients are often thought to have superior neuroplasticity, potentially yielding better outcomes compared to adults. However, limited data exist directly comparing age-stratified outcomes when initial injury severity is matched. Objective: To evaluate and compare outcomes following severe TBI between pediatric and adult patients with similar initial neurological severity, as defined by Glasgow Coma Scale (GCS) scores and pupil reactivity. Methods: This cross-sectional study was conducted at the Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi, from February 2025 to May 2025 after receiving ethical approval from the institutional review board. A total of 300 patients aged 0 to 55 years with severe TBI (GCS score 3–8 and Abbreviated Injury Scale [AIS] head score >3) were enrolled using consecutive non-probability sampling. Participants were stratified into pediatric (0–17 years) and adult (18–55 years) groups. Outcome categories included good recovery, moderate disability, severe disability, vegetative state, and death. Comparative analysis was performed using the chi-square test, with p<0.05 considered statistically significant. Results: Outcome distributions did not significantly differ between groups (p = 0.527). Among adults, 20% had good recovery, 23% moderate disability, 18% severe disability, 17% were vegetative, and 23% died. In the pediatric group, 24% achieved good recovery, 13% had moderate disability, 24% severe disability, 22% were vegetative, and 17% died. Imaging and recovery pattern variations were observed but did not affect overall outcome parity. Conclusion: When initial injury severity is controlled, pediatric and adult patients with severe TBI exhibit comparable short-term outcomes. These findings emphasize the need for standardized, age-inclusive neurocritical care protocols and challenge assumptions of age-dependent prognostication.